Espaço geográfico do Povo Wauja no Parque Indígena do Xingu - Waura, Kuhupi (Universidade Federal de São Carlos, 2024)
The research aimed to record the memory of the Wauja people, focusing on their struggle to conquer and preserve their territory, located in the Xingu Park. To this end, an interview was conducted with members of the community, who shared their stories and challenges throughout this journey. The struggle of the Wauja people is part of a broader battle that involves all indigenous peoples, who continue to resist the threats of companies that seek to exploit their lands, deforestation, environmental contamination, and laws that aim to weaken or eliminate their rights to indigenous lands. The effort to defend indigenous territory and culture remains alive and necessary, to confront the attacks and increasing violence that these peoples face to guarantee their lands, where they can live and grow their food.
Geographical space of the Wauja People in the Xingu Indigenous Park
Keywords: Wauja; Xingu; Território; Terra Indígena; Memória; Territory; Indigenous Lands; Memory; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA